Media Arabic A Coursebook for Reading Arabic News. - Elgibali, Alaa (The American University in Cairo Press, 2014)
".... Introduces the language of newspapers, magazines, and Internet news sites to intermediate- and advanced-level students of Modern Standard Arabic. Using this coursebook, students will be able to master core vocabulary and structures typical of front-page news, recognize various methods of coverage, distinguish fact from opinion, detect bias, and read critically in Arabic. The book enables students to read extended texts with greater accuracy and speed by focusing on the relationships among meaning, linguistic form, and discourse markers. Activities include pre-reading discussions as well as extensive practice on vocabulary use in context, organizing information, skimming, scanning, critical reading, and analyzing content."--Jacket.